ANALISIS KETIMPANGAN PEMBANGUNAN DAN INTERAKSI WILAYAH TERHADAP PERTUMBUHAN EKONOMI DI KAWASAN PURWOMANGGUNG TAHUN 2008-2017 - Yasinta Yovita Prischa Damayanti; Lucia Rita Indrawati; Yustirania Septiani (DINAMIC : Directory Journal of Economic, 2020)
This study aims to analyze the influence of development inequality, regionalinteraction and economic growth between Regencies / Cities in Purwomanggung Region in2008-2017. Economic growth is the dependent variable, while development inequality andregional interactions are independent variables. This research uses the Williamson Indexmethod, the Gravity Index method and panel data analysis using the Fixed Effect Model(FEM) approach. The results show that development inequality is still relatively high andthere is strong interaction in Magelang Regency. However, partially shows that developmentinequality has a negative and significant effect on economic growth, while regionalinteractions have a positive and significant effect on economic growth. However, economicgrowth can be explained simultaneously by Development Inequality and Regional Interaction